64-Slice Computed Tomographic Angiography for the Diagnosis of Intermediate Risk Coronary Artery Disease: An Evidence-Based Analysis (Medical Advisory Secretariat, 2010)
In July 2009, the Medical Advisory Secretariat (MAS) began work on Non-Invasive Cardiac Imaging Technologies for the Diagnosis of Coronary Artery Disease (CAD), an evidence-based review of the literature surrounding different cardiac imaging modalities to ensure that appropriate technologies are accessed by patients suspected of having CAD. This project came about when the Health Services Branch at the Ministry of Health and Long-Term Care asked MAS to provide an evidentiary platform on effectiveness and cost-effectiveness of non-invasive cardiac imaging modalities. After an initial review of the strategy and consultation with experts, MAS identified five key non-invasive cardiac imaging technologies for the diagnosis of CAD. Evidence-based analyses have been prepared for each of these five imaging modalities: cardiac magnetic resonance imaging, single photon emission computed tomography, 64-slice computed tomographic angiography, stress echocardiography, and stress echocardiography with contrast. For each technology, an economic analysis was also completed (where appropriate). A summary decision analytic model was then developed to encapsulate the data from each of these reports (available on the OHTAC and MAS website). The Non-Invasive Cardiac Imaging Technologies for the Diagnosis of Coronary Artery Disease series is made up of the following reports, which can be publicly accessed at the MAS website at: www.health.gov.on.ca/mas or at www.health.gov.on.ca/english/providers/program/mas/mas_about.html: 1. Single Photon Emission Computed Tomography for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis. 2. Stress Echocardiography for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis. 3. Stress Echocardiography with Contrast for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis; 4. 64-Slice Computed Tomographic Angiography for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis. 5. Cardiac Magnetic Resonance Imaging for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis. Pease note that two related evidence-based analyses of non-invasive cardiac imaging technologies for the assessment of myocardial viability are also available on the MAS website: 1. Positron Emission Tomography for the Assessment of Myocardial Viability: An Evidence-Based Analysis. 2. Magnetic Resonance Imaging for the Assessment of Myocardial Viability: an Evidence-Based Analysis. The Toronto Health Economics and Technology Assessment Collaborative has also produced an associated economic report entitled: The Relative Cost-effectiveness of Five Non-invasive Cardiac Imaging Technologies for Diagnosing Coronary Artery Disease in Ontario [Internet]. Available from: http://theta.utoronto.ca/reports/?id=7 OBJECTIVE: The objective of this report is to determine the accuracy of computed tomographic angiography (CTA) compared to the more invasive option of coronary angiography (CA) in the detection of coronary artery disease (CAD) in stable (non-emergent) symptomatic patients. CT ANGIOGRAPHY: CTA is a cardiac imaging test that assesses the presence or absence, as well as the extent, of coronary artery stenosis for the diagnosis of CAD. As such, it is a test of cardiac structure and anatomy, in contrast to the other cardiac imaging modalities that assess cardiac function. It is, however, unclear as to whether cardiac structural features alone, in the absence cardiac function information, are sufficient to determine the presence or absence of intermediate pretest risk of CAD. CTA technology is changing rapidly with increasing scan speeds and anticipated reductions in radiation exposure. Initial scanners based on 4, 8, 16, 32, and 64 slice machines have been available since the end of 2004. Although 320-slice machines are now available, these are not widely diffused and the existing published evidence is specific to 64-slice scanners. In general, CTA allows for 3-dimensional (3D) viewing of the coronary arteries derived from software algorithms of 2-dimensional (2D) images. The advantage of CTA over CA, the gold standard for the diagnosis of CAD, is that it is relatively less invasive and may serve as a test in determining which patients are best suited for a CA. CA requires insertion of a catheter through an artery in the arm or leg up to the area being studied, yet both tests involve contrast agents and radiation exposure. Therefore, the identification of patients for whom CTA or CA is more appropriate may help to avoid more invasive tests, treatment delays, and unnecessary radiation exposure. The main advantage of CA, however, is that treatment can be administered in the same session as the test procedure and as such, it’s recommended for patients with a pre-test probability of CAD of ≥80%. The progression to the more invasive CA allows for the diagnosis and treatment in one session without the added radiation exposure from a previous CTA. The visibility of arteries in CTA images is best in populations with a disease prevalence, or pre-test probabilities of CAD, of 40% to 80%, beyond which patients are considered at high pre-test probability. Visibility decreases with increasing prevalence as arteries become increasingly calcified (coronary artery calcification is based on the Agaston score). Such higher risk patients are not candidates for the less invasive diagnostic procedures and should proceed directly to CA, where treatment can be administered in conjunction with the test itself, while bypassing the radiation exposure from CTA. CTA requires the addition of an ionated contrast, which can be administered only in patients with sufficient renal function (creatinine levels >30 micromoles/litre) to allow for the clearing of the contrast from the body. In some cases, the contrast is administered in patients with creatinine levels less than 30 micromoles/litre. A second important criterion for the administration of the CTA is patient heart rate, which should be less than 65 beats/min for the single source CTA machines and less than 80 beats/min for the dual source machines. To decrease heart rates to these levels, beta-blockers are often required. Although the accuracy of these two machines does not differ, the dual source machines can be utilized in a higher proportion of patients than the single source machines for patients with heart beats of up to 80 beats/min. Approximately 10% of patients are considered ineligible for CTA because of this inability to decrease heart rates to the required levels. Additional contra-indications include renal insufficiency as described above and atrial fibrillation, with approximately 10% of intermediate risk patients ineligible for CTA due these contraindications. The duration of the procedure may be between 1 and 1.5 hours, with about 15 minutes for the CTA and the remaining time for the preparation of the patient. CTA is licensed by Health Canada as a Class III device. Currently, two companies have licenses for 64-slice CT scanners, Toshiba Medical Systems Corporation (License 67604) and Philips Medical Systems (License 67599 and 73260). RESEARCH QUESTIONS: 1. How does the accuracy of CTA compare to the more invasive CA in the diagnosis of CAD in symptomatic patients at intermediate risk of the disease? 2. How does the accuracy for CTA compare to other modalities in the detection of CAD? RESEARCH METHODS: LITERATURE SEARCH: A literature search was performed on July 20, 2009 using OVID MEDLINE, MEDLINE In-Process and Other Non-Indexed Citations, EMBASE, the Cumulative Index to Nursing & Allied Health Literature (CINAHL), the Cochrane Library, and the International Agency for Health Technology Assessment (INAHTA) for studies published from January 1, 2004 until July 20, 2009. Abstracts were reviewed by a single reviewer and, for those studies meeting the eligibility criteria, full-text articles were obtained. Reference lists were also examined for any relevant studies not identified through the search. The quality of evidence was assessed as high, moderate, low or very low according to GRADE methodology. INCLUSION CRITERIA: English language articles and English or French-language HTAs published from January 1, 2004 to July 20, 2009. Randomized controlled trials (RCTs), non-randomized clinical trials, systematic reviews and meta-analyses. Studies of symptomatic patients at intermediate pre-test probability of CAD. Studies of single source CTA compared to CA for the diagnosis of CAD. Studies in which sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV) could be established. HTAs, SRs, clinical trials, observational studies. EXCLUSION CRITERIA: Non-English studies. Pediatric populations. Studies of patients at low or high pre-test probability of CAD. Studies of unstable patients, e.g., emergency room visits, or a prior diagnosis of CAD. Studies in patients with non-ischemic heart disease. Studies in which outcomes were not specific to those of interest in this report. Studies in which CTA was not compared to CA in a stable population. OUTCOMES OF INTEREST): CAD defined as ≥50% stenosis. COMPARATOR: Coronary angiography. MEASURES OF INTEREST: Sensitivity, specificity; Negative predictive value (NPV), positive predictive value (PPV); Area under the curve (AUC) and diagnostic odds ratios (DOR). RESULTS OF LITERATURE SEARCH AND EVIDENCE-BASED ANALYSIS: The literature search yielded two HTAs, the first published by MAS in April 2005, the other from the Belgian Health Care Knowledge Centre published in 2008, as well as three recent non-randomized clinical studies. The three most significant studies concerning the accuracy of CTA versus CA are the CORE-64 study, the ACCURACY trial, and a prospective, multicenter, multivendor study conducted in the Netherlands. Five additional non-randomized studies were extracted from the Belgian Health Technology Assessment (2008). To provide summary estimates of sensitivity, specificity, area under the SROC curve (AUC) and diagnostic odds rations (DORs), a meta-analysis of the above-mentioned studies was conducted. Pooled estimates of sensitivity and specificity were 97.7% (95%CI: 95.5% - 99.9%) and 78.8% (95%CI: 70.8% - 86.8%), respectively. These results indicate that the sensitivity of CTA is almost as good as CA, while its specificity is poorer. The diagnostic odds ratio (DOR) was estimated at 157.0 (95%CI: 11.2 - 302.7) and the AUC was found to be 0.94; however, the inability to provide confidence estimates for this estimate decreased its utility as an adequate outcome measure in this review. This meta-analysis was limited by the significant heterogeneity between studies for both the pooled sensitivity and specificity (heterogeneity Chi-square p=0.000). To minimize these statistical concerns, the analysis was restricted to studies of intermediate risk patients with no previous history of cardiac events. Nevertheless, the underlying prevalence of CAD ranged from 24.8% to 78% between studies, indicating that there was still some variability in the pre-test probabilities of disease within this stable population. The variation in the prevalence of CAD, accompanied with differences in the proportion of calcification, likely affected the specificity directly and the sensitivity indirectly across studies. In February 2010, the results of the Ontario Multi-detector Computed Tomography Coronary Angiography Study (OMCAS) became available and were thus included in a second meta-analysis of the above studies. The OMCAS was a non-randomized double-blind study conducted in 3 centers in Ontario that was conducted as a result of a MAS review from 2005 requesting an evaluation of the accuracy of 64-slice CTA for CAD detection. Within 10 days of their scheduled CA, all patients received an additional evaluation with CTA. Included in the meta-analysis with the above-mentioned studies are 117 symptomatic patients with intermediate probability of CAD (10% - 90% probability), resulting in a pooled sensitivity of 96.1% (95%CI: 94.0%-98.3%) and pooled specificity of 81.5% (95%CI: 73.0% - 89.9%). SUMMARY OF FINDINGS: 1. CTA is almost as good as CA in detecting true positives but poorer in the rate of false positives. The main value of CTA may be in ruling out significant CAD. 2. Increased prevalence of CAD decreases study specificity, whereas specificity is increased in the presence of increased arterial calcification even in lower prevalence studies. 3. Positive CT angiograms may require additional tests such as stress tests or the more invasive CA, partly to identify false positives. 4. Radiation exposure is an important safety concern that needs to be considered, particularly the cumulative exposures from repeat CTAs.